Analysis of Students' Ability in Understanding Concepts, Memorizing Mathematical Formulas - Tiyana, Ilma; Elfrianto, Elfrianto (EDUCTUM: Journal Research, 2023)
Understanding of mathematical concepts is still low among students at both primary and secondary levels. The use of a learning approach must be the main concern to obtain a good understanding of the concept. This research is to find out whether students' understanding of mathematical concepts is taught using an understanding of mathematical concepts taught using a conventional approach. The population in this study was all 30 class XI PAB HELVETIA students. Class sampling was carried out using a random sampling technique which began with testing class equality. Data was collected using instruments in the form of descriptions and using test techniques. The results of the research show that students' understanding of mathematical concepts taught using a conventional approach is still not good for students' understanding in learning geometry.